Evaluation of Pond/Wetland/Vegetative Filter System to Treat Beef Manure Pile and Outdoor Confinement Area Runoff - Mejia Franco, Maria Juliana (Université d'Ottawa / University of Ottawa, 2018)
Regulations with respect to the storage and handling of animal waste by livestock operations state that no person shall keep animals in a permanent confinement area unless there is a nutrient management strategy. Various studies indicate that constructed wetlands and vegetative filters are effective add-on technologies to supplement the treatment provided by conventional sedimentation pond systems in livestock operations. Seven months of data from a Pond/Wetland/Vegetative Filter system receiving cattle feedlot runoff were used to i) evaluate its efficiency removing organic matter, solids and nutrients from water, (ii) quantify constructed wetland kinetic removal rates described by the P-C-k model and examine the impact of temperature, (iii) evaluate and compare the performance of a two types of vegetative filter systems at different hydraulic loading rates; and (iv) recommend an optimum management option with design loading for beef producers. Results indicate that the effect of isolated rain events on the performance of the wetland showed to be contingent on the intensity of the event, former humidity conditions of the feedlot and the hydraulic capacity of the wetland. This experiment suggests that even relatively small VFSs or short FPs can markedly improve quality of runoff from livestock operations, and that it is possible to achieve significant mass and concentration removals if they are properly operated and maintained in conjunction with a pre-treatment system. The Pond/Wetland/Vegetative Filter system was effective at reducing Chemical Oxygen Demand COD (+92%), Total Phosphorus (+93%), Orthophosphate as P (+91%), Total Inorganic Nitrogen (+96%), Ammonia as N (+97%) and Nitrate as N (+82%) from manure and exercise yard runoff, providing a cost-effective treatment option for beef producers.
Keywords: Constructed wetland; Vegetative filter; Pond; Runoff; Wastewater; Treatment; System; Feedlot; Manure pile; P-C*-k model; Filter strip; Vegetated filter; Livestock